Application of Stereo Vision to Control the Movement of the Robot Arm Towards the Position of Red Chilies - I Dewa Made Subrata; Ahmad Dzaky Baiquni (The University of Lampung, 2024)
The trend of decreasing young workers in the agricultural sector needs to be anticipated by developing intelligent machines known as agricultural robots. This research aims to apply a stereo vision system to control the movement of the robot's grip towards the 3D position of the red chili fruit. The stereo vision system installed on the robot waist (joint-2) is used to capture plant images and process them using HSV masking filters and triangulation principal to obtain the 3D center point position of the fruit. The robot joint movement is calculated using geometric based inverse kinematics. The research results show that the average accuracy of the stereo vision system is 93.9 %. The average grip positioning accuracy is 95.6 % to the actual chili fruit position and 98.5 % to the stereo vision calculation value. The average stability of the stereo vision values is 99.5 %, while the average positioning stability of the robot's grip is 99.6 %. Time consumption for image processing is 0.053 s while time consumption for robot grip movement is 9 s. Therefore, the stereo vision system can be used to control robot's grip movement with a good accuracy. Keywords: Red chili fruit, Robot arm, Stereo vision, Three-dimensional position.